27.1k views
0 votes
Given that f(x) = x2 –3x – 40 and g(x) = x +5, find (f +g)(x) and express

the result in standard form.

User RavenMan
by
5.2k points

1 Answer

4 votes

Answer:


(f+g)(x)=x^2-2x-35

Explanation:

So we have the two functions:


f(x)=x^2-3x-40\text{ and } g(x)=x+5

And we want to find (f+g)(x). This is the same as:


(f+g)(x)=f(x)+g(x)

Substitute:


=(x^2-3x-40)+(x+5)

Combine like terms:


=x^2+(-3x+x)+(-40+5)

Add:


=x^2-2x-35

And we're done!

User Herzmeister
by
4.9k points